Mammary carcinoma in aged gerbil mothers after endocrine disruption in pregnancy and lactation - Ruiz, Thalles Fernando Rocha [UNESP]; Colleta, Simone J. [UNESP]; Leonel, Ellen C R; Taboga, Sebastião Roberto [UNESP] (Bioscientifica, 2021)
Compounds that trigger breast cancer onset and establishment are of great interest in biological research. Endocrine disruptors are relevant because they initiate carcinogenesis by changing endocrine pathways. Bisphenol A (BPA), as a ubiquitous xenoestrogen, is largely associated with dysfunctions in the female reproductive system and associated organs. This study proposes an investigation of the mammary gland (MG) in aged Mongolian gerbil (Meriones unguiculatus) mothers after their exposure to BPA in two windows of morphophysiological plasticity: pregnancy and lactation. A low dose (50 μg/kg) and a high dose (5000 μg/kg) of BPA were considered, and results showed few differences between them. As expected, we observed contrasts among control and BPA-exposed MG. The control groups presented a regressive phase with high apoptotic activity and elastic stroma. However, BPA damaged mammary tissue and provoked multifocal carcinoma development supported by an apparent epithelial-mesenchymal transition (EMT) and reactive stroma establishment. BPA remodeled stromal fibers deposition and enhanced the recruitment of tumor-associated cells, contributing to a tumoral microenvironment. Overexpression of TGF-β1 was induced by BPA in the epithelial compartment of exposed MG, and increased expression of metalloproteinases (MMP-2, MMP-3, MMP-9) was present in carcinoma cells. In conclusion, exposure of mothers to BPA during the gestational/lactational window of susceptibility leads to carcinogenic impacts with aging.
Keywords: bisphenol A; epithelial-mesenchymal transition; extracellular matrix; mammary gland; TGF-beta